A Mother's Cry : A Memoir of Politics, Prison, and Torture under the Brazilian Military Dictatorship - Sattamini, Lina Penna (Book collections on Project MUSE., 2010)
Testimonial and memoir of Lina Penna Sattamini's attempts to save her son from possible death at the hands of Brazil's military dictatorship, which had accused him of subversive activities in the early 1970s.